2013
DOI: 10.1097/jto.0b013e31828c3950
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 Study of Pemetrexed and Itraconazole as Second-Line Therapy for Metastatic Nonsquamous Non–Small-Cell Lung Cancer

Abstract: Purpose Preclinical studies suggested that the oral anti-fungal agent itraconazole specifically inhibits proliferation, migration, and tube formation of endothelial cells. Itraconazole has potent anti-angiogenic activity and enhances the efficacy of cytotoxic chemotherapy in multiple primary xenograft lung cancer models. Based on these data, we performed an exploratory clinical study assessing the efficacy of itraconazole with cytotoxic chemotherapy in the treatment of patients with advanced lung cancer. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
109
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(110 citation statements)
references
References 17 publications
0
109
1
Order By: Relevance
“…Phase III trials of the VEGFR inhibitor ramucirumab reported prolonged OS in non-small cell lung, gastric and colorectal cancer, (45)(46)(47)(48). Considering the results of the clinical trials using P-gp inhibitor or antiangiogenic agents (41,(43)(44)(45)(46)(47), the clinical efficacy of itracoanzole treatment in various types of cancer (Table II) implicated the additional anticancer activities, which was demonstrated in preclinical studies (Table I).…”
Section: Clinical Datamentioning
confidence: 99%
“…Phase III trials of the VEGFR inhibitor ramucirumab reported prolonged OS in non-small cell lung, gastric and colorectal cancer, (45)(46)(47)(48). Considering the results of the clinical trials using P-gp inhibitor or antiangiogenic agents (41,(43)(44)(45)(46)(47), the clinical efficacy of itracoanzole treatment in various types of cancer (Table II) implicated the additional anticancer activities, which was demonstrated in preclinical studies (Table I).…”
Section: Clinical Datamentioning
confidence: 99%
“…Upon validation of its antiangiogenic and antitumor activity in a number of models both in vitro and in vivo (8,10,11), it entered multiple phase 2 clinical trials for treating cancer. To date, the pilot trials in nonsmall cell lung cancer, prostate cancer, and basal cell carcinoma have been completed; itraconazole has been shown to increase the progression-free and overall survival of patients taking the drug (12)(13)(14). Additionally, retrospective studies assessing the outcomes of patients with ovarian cancer and recurrent triplenegative breast cancer taking itraconazole have revealed significant increases in overall survival (15)(16)(17), which are likely to be attributable, at least in part, to the antiangiogenic activity of itraconazole.…”
Section: Significancementioning
confidence: 99%
“…The suppression of tumour growth with itraconazole treatment has been demonstrated in non-small cell lung cancer xenografts (8,18). In one such study, growth was reduced by 72 and 79% (P<0.001) in two primary xenograft models (8).…”
Section: Itraconazole and Angiogenesismentioning
confidence: 95%
“…As well as inhibiting cell proliferation in response to angiogenesis factors (VEGF and fibroblast growth factor), the migration and formation of tube networks were also prevented. These are necessary for capillary bed production; therefore, the area of tumour vascularity significantly decreased (8,18). In addition, itraconazole has been demonstrated to reduce pleural effusion volumes, the number of pleural tumour foci and VEGF-C levels in xenograft models with Lewis lung carcinoma (7).…”
Section: Itraconazole and Angiogenesismentioning
confidence: 99%